Hydrogenated Planar Aluminum Clusters: A Density Functional Theory Study - Changhong Yao; Meijiao Wang; Lianzhen Cao (Molecules)
The low-lying energy structures of small planar aluminum clusters Aln (n = 3–6, 8–10), hydrogenated small planar aluminum clusters AlnHm (n = 3–8, m = 1–2) and the lowest-energy structure of AlnHm (n = 6–10, m = 0–2) are determined by density functional theory (DFT) calculations. Many stable planar structures have been found; some are consistent with the reported ones, and some are new configurations. The preservation of planar cluster structures has been observed during the dissociative adsorption of H2.Hydrogen is adsorbed at different positions on planar aluminum clusters. Dissociative adsorption configurations of the planar structure and lowest-energy structure experienced a decrease in hydrogen adsorption energy with an increase in cluster size. Among the clusters we calculated, Al4H1 and Al4H2 have the highest HOMO-LUMO gap, indicating that they may be more abundant than other clusters. The geometric structure and electronic properties of these clusters are also discussed.